Міфологізм у символістській прозі Клима Поліщука - Костиря, Б. (Літературознавчі обрії. Праці молодих учених, 2010)
The particularities of mythology in symbolist prose by Klym Polishchuk are explained in the article. There are two time planes of plot evolvement in fantastic stories by Klym PolishchukG past and present. Fantastic events in the past have continuation in t